Rare bird documentation form for Northern Goshawk at Sweet Marsh, 1981 - Hays, Russellet al (1981)
Rare bird documentation form for a Northern Goshawk at Sweet Marsh in Bremer County, IA on December 19, 1981. Epson - sheet feed